(untitled) (Fourth World Journal, 2025)
This article reviews Qaqamiigux: Traditional Foods and Recipes from the Aleutian and Pribilof Islands by Suanne Unger, emphasizing the vital role of native foods in Unangan culture. The book documents a community-wide effort to revitalize traditional food practices amidst modern health challenges and cultural disconnection. It explores historical, environmental, and socioeconomic factors shaping food choices, while providing detailed guidance on harvesting and preparing marine mammals, fish, plants, and other native foods.